Government Performance and Democracy: Survey Experimental Evidence from 12 Countries during COVID-19 - Becher, Michael; Longuet Marx, Nicolas; Pons, Vincent; Brouard, Sylvain; Foucault, Martial; Galasso, Vincenzo; Kerrouche, Eric; León Alfonso, Sandra; Stegmueller, Daniel (The University of Chicago Press, 2024)
Crises of the magnitude of the COVID-19 pandemic may plausibly affect deep-seated attitudes of a large fraction of citizens. In particular, outcome-oriented theories imply that leaders’ performance in response to such adverse events shapes people’s views about the government and about democracy. To assess these causal linkages empirically, we use a preregistered survey experiment covering 12 countries and 22,500 respondents during the pandemic. Our design enables us to leverage exogenous variation in evaluations of policies and leaders with an instrumental variables strategy. We find that people use information on both health and economic performance when evaluating the government. In turn, dissatisfaction with the government decreases satisfaction with how democracy works, but it does not increase support for nondemocratic alternatives. The results suggest that comparatively bad government performance mainly spurs internal critiques of democracy.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 3 - Salud y bienestar; ODS 10 - Reducción de las desigualdades